2019
DOI: 10.1101/637785
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Compromised function of the ESCRT pathway promotes endolysosomal escape of tau seeds and propagation of tau aggregation

Abstract: Intercellular propagation of protein aggregation is emerging as a key mechanism in the progression of several neurodegenerative diseases, including Alzheimer's Disease and frontotemporal dementia. However, we lack a systematic understanding of the cellular pathways controlling prion-like propagation. To uncover such pathways, we performed CRISPR interference (CRISPRi) screens in a human cellbased model of propagation of tau aggregation. Our screens uncovered that knockdown of several components of the ESCRT ma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 71 publications
1
33
0
Order By: Relevance
“…In accordance with previous studies (Guo et al, 2016a; McEwan et al, 2017), we show that seeding is not rate-limiting and that seeded aggregation is a rapid process that occurs within 12 h after the entry of the amyloid template into the cells. Compared to other assays (Guo et al, 2016a;Guo et al, 2016b;McEwan et al, 2017;Chen et al, 2019Chen et al, , 2020, we were able to record in real time the cellular conversion of endogenously expressed RD upon exogenous addition of K18 fibrils, using a live-cell analysis system consisting of an automated microscope embedded within the incubator (IncuCyte System from Essen Bioscience). This allowed us to observe the kinetics of seeding, starting from the exogenous addition of fibrils to the culture and ending several days after the endogenous formation of aggregates had occurred.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with previous studies (Guo et al, 2016a; McEwan et al, 2017), we show that seeding is not rate-limiting and that seeded aggregation is a rapid process that occurs within 12 h after the entry of the amyloid template into the cells. Compared to other assays (Guo et al, 2016a;Guo et al, 2016b;McEwan et al, 2017;Chen et al, 2019Chen et al, , 2020, we were able to record in real time the cellular conversion of endogenously expressed RD upon exogenous addition of K18 fibrils, using a live-cell analysis system consisting of an automated microscope embedded within the incubator (IncuCyte System from Essen Bioscience). This allowed us to observe the kinetics of seeding, starting from the exogenous addition of fibrils to the culture and ending several days after the endogenous formation of aggregates had occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Published data suggest that exogenous Tau fibrils can enter the cells by endocytosis or by micropinocytosis, being directed to late endosomes or lysosomes (Frost et al, 2009b;Wu et al, 2013;Holmes et al, 2013;Calafate et al, 2015Calafate et al, , 2016Papadopoulos et al, 2017;Rauch et al, 2018). These Tau-containing vesicular structures could undergo lysosomal membrane permeabilization, thereby allowing the aggregates to escape into the cytosol and induce autophagy (Calafate et al, 2016;Papadopoulos et al, 2017;Chen et al, 2019). Here, we did not address the mechanisms of entry and fate of exogenous fibrils, but we rather aimed to analyze the fate of endogenously formed Tau fibrils in a model that allows monitoring the propagation of the amyloid conformation.…”
Section: Fate Of Tau Fibrils In Neuronal Cellsmentioning
confidence: 99%
“…The DELE1 coding sequence was cloned from human cDNA and inserted into pMK1253 36 through Gibson assembly to generate a DELE1-mClover tagged protein under the EIF1A promoter (pXG286). To obtain a construct that enabled integrate DELE1-mClover at the safe harbor locus (pXG289), the EIF1A promoter-DELE1-mClover cassette was PCR-amplified from pXG286, and inserted between the SpeI and MluI sites of the AAVS-1-targeting vector pMTL3 37 .…”
Section: Methodsmentioning
confidence: 99%
“…This accumulation also damages the endolysosomal membrane resulting in the release of amyloids in the cytosol, which contributes to cytotoxicity and the propagation of amyloids [ 90 , 91 , 92 ]. In this context, the ESCRT machinery is key for membrane repairing processes [ 93 ] and it was recently shown that a compromised function of the ESCRT machinery promotes the release and propagation of Tau protein [ 94 ].…”
Section: At the Mvb: The Coordinated Conveyance Of Processing And mentioning
confidence: 99%